2017
DOI: 10.1002/ppul.23662
|View full text |Cite
|
Sign up to set email alerts
|

Oligohydramnios compromises lung cells size and interferes with epithelial–endothelial development

Abstract: Although, the smaller size of the lung could be explained by a decreased of lung fluids, our data suggest that increased of external compression secondary to severe oligohydramnios can compromise cell size and interfere with epithelial and endothelial development. Type I epithelial cells could have an unrecognized key role in the differentiation of the distal lung mediated by mechanical signals. Pediatr Pulmonol. 2017;52:746-756. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…As patients with fetal congenital defects were excluded from the study, this result does not represent pulmonary hypertension caused by diagnosed congenital heart disease. This result is also compatible with other studies reporting compromised lung development due to oligohydramnios [8,18,19]. Pulmonary hypertension is also associated with prematurity and its treatment side effects e.g.…”
Section: Discussionsupporting
confidence: 92%
“…As patients with fetal congenital defects were excluded from the study, this result does not represent pulmonary hypertension caused by diagnosed congenital heart disease. This result is also compatible with other studies reporting compromised lung development due to oligohydramnios [8,18,19]. Pulmonary hypertension is also associated with prematurity and its treatment side effects e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Mechanical force effects on lung development have long been recognized: severe pulmonary hypoplasia associated with oligohydramnios represents the most extreme example. Najrana and colleagues 31 show that oligohydramnios induced by amniotic sac puncture in mice alters fetal (E18.5) lung cell morphology and cell-type abundance, possibly through the effects on cellular differentiation and apoptosis. Although the authors concluded that cell proliferation was not altered as PCNA of separate cells was unaffected, surely this result is likely to be cell-type dependent: progenitor cells in the lung are not uniformly distributed.…”
Section: Experimental Studies In Lung Developmentmentioning
confidence: 99%
“…The alveolar stage of differentiation, i.e ., development of mature alveolar ducts and alveoli occurs several days after birth (P5‐P30), a spurt of alveolar multiplication followed by one of arterial multiplication. Najrana at al . describe amniotic sac drainage from E14.5 until E18.5, comparable to human extreme preterm birth.…”
mentioning
confidence: 93%
“…Animal models have shed light on the pathogenesis of forms of pulmonary hypoplasia . Recently in this journal, the study by Najrana et al . advances our understanding of mechanisms underlying distal lung dysplasia in mid‐trimester PPROM by using a mouse model that developmentally mimics human mid‐trimester PPROM.…”
mentioning
confidence: 99%
See 1 more Smart Citation